IMPACT OF OVO DIGITAL WALLET ON MSME WELFARE IN SURAKARTA - Fabian Kusuma Ramadhan; Agustinus Suryantoro; Dyah Maya Nihayah (Journal of Applied Economics in Developing Countries, 2023)
This study examines the impact of using the OVO digital wallet on the turnover of street vendors in Surakarta. The informal economy, particularly street vendors, plays a significant role in Indonesia's economy. This research utilizes multiple linear regression analysis on questionnaire data to understand the influence of OVO usage. Findings indicate that OVO usage increases vendor welfare through higher income turnover, supported by the ease of use, mobility, reputation, trust, and security of the fintech product. Jebres, with its large number of vendors around Sebelas Maret University, shows significant influence.